Examining modus operandi in stranger child abduction: A comparison of attempted and completed cases. Issue 2 (9th January 2019) - Collie, Craig J.R.; Shalev Greene, Karen
Abstract: Existing inquiries purporting to study and describe offender behaviour in stranger child abduction (SCA) have utilised an overly narrow definition of modus operandi (MO), focusing only on very outset of the offence. The study aims to reflect changes that occur as the offence proceeds and to examine whether differentiating between attempted and completed cases can provide greater understanding of MO in SCA. The MO utilised by offenders in 78 cases of SCA retrieved from publicly available U.K. sources were examined. Descriptive analysis was used to determine which types of behaviour were present. Multidimensional scaling was used to categorise these behaviours and to establish whether any relationships existed between them, with view to ascertaining whether there were any clear patterns among strategies. Results found support for differentiating attempted and completed offences, with the analysis highlighting that offenders who utilised multiple means of control, who were more aggressive, and who shifted their MO from one theme to another, were more likely to complete the offence. The study concludes that more nuanced categorisations of SCA offending approaches, which reflect change over time, are required, and argues for additional, contextual information to be incorporated into future work.